2021
DOI: 10.1044/2021_jslhr-20-00278
|View full text |Cite
|
Sign up to set email alerts
|

Speech Intensity Response to Altered Intensity Feedback in Individuals With Parkinson's Disease

Abstract: Purpose Hypophonia (low speech intensity) is the most common speech symptom experienced by individuals with Parkinson's disease (IWPD). Previous research suggests that, in IWPD, there may be abnormal integration of sensory information for motor production of speech intensity. In the current study, intensity of auditory feedback was systematically manipulated (altered in both positive and negative directions) during sensorimotor conditions that are known to modulate speech intensity in everyday cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Hyperactive auditory feedback responses in persons with PD who are off medication have been noted by multiple altered auditory feedback behavioral studies for vocal f o [72][73][74][75] and for vocal SPL [73]. Reduced adaptive responses were also observed in several studies carried out with persons with PD (vocal f o : [69], vocal SPL: [87]). Overall, these studies suggest that persons with PD have hyperactive auditory feedback and weakened auditory-motor integration that causes impaired feedforward motor control.…”
Section: Discussionmentioning
confidence: 89%
“…Hyperactive auditory feedback responses in persons with PD who are off medication have been noted by multiple altered auditory feedback behavioral studies for vocal f o [72][73][74][75] and for vocal SPL [73]. Reduced adaptive responses were also observed in several studies carried out with persons with PD (vocal f o : [69], vocal SPL: [87]). Overall, these studies suggest that persons with PD have hyperactive auditory feedback and weakened auditory-motor integration that causes impaired feedforward motor control.…”
Section: Discussionmentioning
confidence: 89%
“…On the one hand, although it has been shown that modi ed auditory feedback impacts PD patients differently from controls [14][15][16] , this observation has not been previously included in the design of speechbased screening tests. We integrate this observation by asking participants to complete the classic DDK task under different auditory feedback conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to dysarthria, it has been shown that the effects produced on the ongoing speech by an unexpected modulation of the auditory feedback differ between PD patients and healthy controls [14][15][16] . This result made researchers hypothesize that PD patients have abnormal speech auditory-motor integration.…”
Section: Introductionmentioning
confidence: 99%
“…El deterioro motor temprano propicia dificultades para la articulación del habla y para la escritura; los movimientos manuales anormales aparecen desde el inicio, característica que hace que el deterioro de la escritura en la EP sea atribuido al déficit motor (Mollaei et al, 2019;Senthinathan et al, 2021). Sin embargo, la escritura ha sido un terreno que sólo recientemente ha sido explorado dentro de este tipo de patología.…”
unclassified